Innovative Work Behavior of Vocational High School Teachers: the Role of Perceived Organizational Support and Knowledge Sharing - Nadia, Farahita Saffa; Kusmaryani, Rosita Endang (World Psychology, 2025)
Innovative work behavior in teachers is a determining factor in achieving competitive advantage and organizational success, especially in school organizations. However, the majority of teachers still tend to be reluctant to innovate in their work, which impacts the quality of vocational high school graduates, which is still relatively low. Several previous studies have shown the role of perceived organizational support and knowledge sharing. This study uses a quantitative approach with a survey research type. The subjects in this study were 277 vocational high school teachers in Kebumen Regency, with a multistage random sampling technique. Innovative work behavior was measured using the Innovative Work Behavior Scale from Jong and Hartog (2010). POS was measured using the Survey of perceived organizational support (SPOS) from Eisenberger et al., (1986), and knowledge sharing was measured using the Knowledge sharing behavior scale from Kim et al., (2013). Content validity was tested using Gregory analysis, and obtained a score of 1 (> 0.8). Reliability test using Alpha Croncbach's and obtained results on the Innovative Work Behavior Scale is 0.899, Survey of perceived organizational support (SPOS) is 0.926 and Knowledge sharing behavior scale is 0.842. Data analysis using multiple linear regression test using SPSS Version 25 program. The results of the study show that perceived organizational support and knowledge sharing are predictors of innovative work behavior in vocational high school teachers.